Estimation of Eyelid Pressure Using a Blepharo-Tensiometer in Patients with Functional Nasolacrimal Duct Obstruction - Jinsoo Kim; Sang-Mok Lee; Youn Joo Choi; Min Joung Lee (Journal of Ophthalmology)
Purpose. To compare the eyelid pressure between patients with functional nasolacrimal duct obstruction (FNLDO) and normal controls using blepharo-tensiometer, and to evaluate the relationship between eyelid pressure and the outcomes of silicone intubation (SI) in patients with FNLDO. Study design. Prospective case-control study. Methods. We enrolled 36 eyes of 36 patients with suspected FNLDO who underwent SI and 36 healthy eyes of age-matched controls. One eye of each patient with FNLDO was randomly selected for analysis. The eyelid pressure was estimated using a blepharo-tensiometer and compared between the control and FNLDO groups. The relationship between eyelid pressure and clinical variables was analyzed. The outcomes of SI were assessed at 6 months after surgery using subjective and objective criteria. Results. The eyelid pressure was significantly lower in the FNLDO group than in the control group P=0.008. In the control group, the eyelid pressure was correlated with age P<0.001 and lower eyelid laxity P=0.016. In the FNLDO group, the eyelid pressure was only correlated with age P<0.001. The success rate of SI for FNLDO was 69.4% (25 of 36 eyes). The eyelid pressure was higher in the surgical success subgroup than in the failure subgroup, although the difference was not statistically significant P=0.08. Conclusions. Our results suggest that the eyelid pressure measured using a blepharo-tensiometer has a diagnostic value since it is decreased in patients with FNLDO. The role of eyelid pressure as a possible predictor of the outcomes of SI for FNLDO should be investigated in further studies. This trial is registered with KCT0002828.